Age polyethism in the swarm-founding wasp Metapolybia miltoni (Andena & Carpenter) (Hymenoptera: Vespidae; Polistinae, Epiponini) - Chavarria, Laura; Noll, Fernando Barbosa [UNESP] (Univ Estadual Feira Santana, 2013)
In Epiponini division of labor is associated with age polyethism and individual task specialization. We observed worker activities in three colonies of Metapoybia miltoni in Brazil. We analyzed differences of task allocation among age groups. Old workers tend to forage more than young, but age polyethism was less evident in other tasks. Age composition of population could be a determinant factor in task allocation. Workers are probably allocating to perform tasks according to colony needs, and not to individual's age. Considering age population in studies of division of labor could help to understand how colonies respond to different situations.
Keywords: Division of labor; Social wasps; Workers